UPAYA PENINGKATAN PRODUKTIFITAS KAMBING MELALUI PERSILANGAN KAMBING LOKAL DENGAN KAMBING BOER DI DESA CENDI MANIK KECAMATAN SEKOTONG TENGAH - Lalu Ahmad Zaenuri; I Wayan Lanus Sumadiasa; Rodiah Rodiah (Jurnal Abdi Insani, 2022)
The topic of service was chosen based on the consideration that the goat population is relatively high but the goat species that is kept is a Kacangt goat with low productivity, so it needs to be crossed with a Boer goat. The purpose of the services were firstly, to explain the advantages and disadvantages of several types of goats and how to choose superior goat breeds. Secondly, to explain the advantages of Boer goats, characteristics of aestrus goats, methods of crossbreeding and how to evaluate pregnant and non-pregnant goats. The implementation method is the Innovative Approach which emphasizes the participatory approach of the training participants. The results of the evaluation found that the material presented was in accordance with the needs of the breeders at the service location, because so far most of the farmers kept Kacang goats. All the training participants considered that this training material was very useful for them so that the participants were very enthusiastic and interested in cross-breeding their goats with Boer goats. It was concluded that this training had succeeded in increasing the knowledge of farmers on how to select superior goats and how to cross Kacang goats with Boer goats. For follow-up, it is recommended that farmers could contact the inseminator at the nearest Puskeswan to get insemination services using frozen Boer goat semen.